Perceived Impact of Music Tourism and Support for Music Tourism among Local Communities: The Moderating Effect of Psychological Egoism - Choong, Yuen Onn; Kuek, Thiam Yong; Chai, Bobby Boon Hui; Khor, Saw Chin; Low, Mei Peng; Yap, Timothy Tzen Vun (Media Konservasi, 2024)
Music tourism, a growing segment of the tourism industry, has significant socio-economic benefits but also poses environmental challenges. This study investigates the relationship between the perceived impact of music tourism and local community support in Kuala Lumpur, Malaysia, with a particular focus on the moderating effect of psychological egoism. Using Partial Least Square Structural Equation Modeling (PLS-SEM) and survey data from 134 local residents, we found that positive perceived impacts of tourism correlate with higher community support. However, psychological egoism influences this relationship, as individuals with higher egoism levels still support music tourism despite recognizing its negative impacts. These findings highlight the need for targeted educational campaigns to promote environmental sustainability and community well-being. Local governments and event organizers should focus on enhancing the positive impacts and mitigating the negative ones to foster sustainable tourism practices that align with conservation goals and contribute to UNESCO Sustainable Development Goal 8.